2013
DOI: 10.1097/ede.0b013e31829d5c93
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Methylmercury Exposure and Genetic Predisposition to Cognitive Deficit at Age 8 Years

Abstract: Background: Cognitive consequences at school age associated with prenatal methylmercury exposure may need to take into account nutritional and socio-demographic cofactors as well as relevant genetic polymorphisms. Methods: A sub-sample (n = 1311) of the Avon Longitudinal Study of Parents And Children (Bristol, UK) was selected and mercury concentrations were measured in freeze-dried umbilical cord tissue as a measure of methylmercury exposure. A total of 1135 children had available data on 247 single-nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 48 publications
1
53
1
Order By: Relevance
“…29 Some common genetic polymorphisms seem to increase the vulnerability of the developing brain to methylmercury toxicity. 30 Functional MRI scans of people exposed prenatally to excess amounts of methylmercury showed abnormally expanded activation of brain regions in response to sensory stimulation and motor tasks (figure 2). 31 Because some adverse effects might be counterbalanced by essential fatty acids from seafood, statistical adjustment for maternal diet during pregnancy results in stronger methylmercury effects.…”
Section: Introductionmentioning
confidence: 99%
“…29 Some common genetic polymorphisms seem to increase the vulnerability of the developing brain to methylmercury toxicity. 30 Functional MRI scans of people exposed prenatally to excess amounts of methylmercury showed abnormally expanded activation of brain regions in response to sensory stimulation and motor tasks (figure 2). 31 Because some adverse effects might be counterbalanced by essential fatty acids from seafood, statistical adjustment for maternal diet during pregnancy results in stronger methylmercury effects.…”
Section: Introductionmentioning
confidence: 99%
“…(e) It remains possible that differences in metabolism, perhaps the result of different genotypes in either the mother or offspring, may have a confounding effect (e.g. Julvez et al, 2013) or make some individuals susceptible even when the population is not.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, epidemiological studies have explored gene-mercury interactions for human mercury neurotoxicity and identified possible genetic risk modifiers for mercury exposure [5659]. Possible gene-environment interactions with mercury for heart rate variability outcomes might be explored in future research.…”
Section: Discussionmentioning
confidence: 99%